Y-U ADVANCEMENT PYLOROPLASTY AS AN ALTERNATIVE TO TRANSVERSE PYLOROPLASTY TO RELIEVE PYLORIC STENOSIS IN DOGS - A. Safdar; M. Arif Khan; M. M. Ali; M. H. Saleem; M. Ijaz (Journal of Animal and Plant Sciences, 2013)
Two commonly used surgical procedures i.e., transverse pyloroplasty and Y-U advancement flap pyloroplasty were compared to observe the relieve of pyloric stenosis in dogs. In this experimental design, twelve healthy mongrel dogs were used with further division of three groups, A, B and C comprising of four dogs in each group. The dogs of group A were subjected to Transverse pyloroplasty whereas Y-U advancement pyloroplasty was performed on dogs of group B. The group C was kept as control. Both surgical techniques were assessed by normal feeding pattern, vomiting, hematemesis, hemochazia, duration of external wound healing and contrast radiography. Results indicated that Y-U advancement flap pyloroplasty was superior to the transverse pyloroplasty in terms of simplicity, safety, maximal channel size with minimal operating time and better gastric emptying time.
Keywords: Dogs; Pylorus; Pyloroplasty; Contrast radiography